Repositioning N-Acetylcysteine (NAC): NAC-Loaded Electrospun Drug Delivery Scaffolding for Potential Neural Tissue Engineering Application - Gillian D. Mahumane; Pradeep Kumar; Viness Pillay; Yahya E. Choonara (MDPI AG, 2020)
Traumatic brain injury (TBI) presents a serious challenge for modern medicine due to the poor regenerative capabilities of the brain, complex pathophysiology, and lack of effective treatment for TBI to date. Tissue-engineered scaffolds have shown some experimental success in vivo; unfortunately, none have yielded consummate results of clinical efficacy. N-acetylcysteine has shown neuroprotective potential. To this end, we developed a N-acetylcysteine (NAC)-loaded poly(lactic-co-glycolic acid) (PLGA) electrospun system for potential neural tissue application for TBI. Scanning electron microscopy showed nanofiber diameters ranging 72-542 nm and 124-592 nm for NAC-free and NAC-loaded PLGA nanofibers, respectively. NAC loading was obtained at 28%, and drug entrapment efficacy was obtained at 84%. A biphasic NAC release pattern that featured an initial burst release (13.9%) stage and a later sustained release stage was noted, thus enabling the prolonged replenishing of NAC and drastically improving cell viability and proliferation. This was evidenced by a significantly higher cell viability and proliferation on NAC-loaded nanofibers for rat pheochromocytoma (PC12) and human glioblastoma multiform (A172) cell lines in comparison to PLGA-only nanofibers. The increased cell viability and cell proliferation on NAC-loaded nanofiber substantiates for the repositioning of NAC as a pharmacological agent in neural tissue regeneration applications.